PENGARUH PRESTASI KERJA, PENGALAMAN KERJA, DAN PENDIDIKAN TERHADAP PROMOSI JABATAN DI RSI IBNU SINA SIMPANG EMPAT PASAMAN BARAT - Yurasti Mahdona (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
This research was conducted on employees’ of Islamic Hospital Ibnu Sina Simpang EmpatIn West Pasaman. The purpose of this study to determine the effect of Job Performance,Work Experience, and Education Against Job Promotion At RSI Ibnu Sina SimpangEmpatin West Pasaman. This research included into the research using field research thatis quantitative, with the number of samples of 50 respondents.The data was collected bydistributing questionnaires using a 5-point likert scale to measure 26 statement item.Dataprocessed on SPSS version 19.0.The statement Tested by using test of validity andreliability.The multiple regression analysis showed that each of the variables used in thisstudy has a regression equation as follows: Y = 1,450 +0,628X1 + (-0,030)X2 + 0,073 X3+ e. The result of the analysis shows Job performance,Work Experience, and Educationsignificant effect simultaneously on Promotion at RSI Ibnu Sina Simpang Empat WestPasaman. Job performance a significant effect partial on Promotion at RSI Ibnu SinaSimpang Empat West Pasaman. Experience and education does not have an effect on thepromotion At RSI Ibnu Sina SimpangEmpatWest PasamanKeywords:Promotion, Job Performance, Work Experience, and Education